Computed tomography versus lower endoscopy as initial diagnostic method for evaluating patients with hematochezia at emergency room. Issue 22 (29th May 2020) - Lee, Hee Sung; Kang, Sun Hyung; Rou, Woo Sun; Eun, Hyuk Soo; Joo, Jong Seok; Kim, Ju Seok; Lee, Eaum Seok; Moon, Hee Seok; Kim, Seok Hyun; Sung, Jae Kyu; Lee, Byung Seok; Jeong, Hyun Yong
Abstract : Abstract: For acute lower gastrointestinal bleeding (LGIB), lower gastrointestinal endoscopy is the preferred initial diagnostic test. However, it is difficult to perform urgently. Computed tomography (CT) is a convenient alternative. This study aimed to determine the diagnostic performance of CT compared to lower endoscopy as an initial test for evaluating acute LGIB. The medical records of 382 patients who visited our emergency department with hematochezia between January 2012 and January 2017 were retrospectively analyzed. Of them, 112 underwent CT, 65 underwent colonoscopy, and 205 underwent sigmoidoscopy as an initial test. For each method, sensitivity, specificity, positive predictive value, and negative predictive value were calculated upon active bleeding site detection and LGIB etiology diagnosis. The sensitivity, specificity, positive predictive value, and negative predictive value of CT for active bleeding site detection were 85.7%, 100%, 100%, and 96.9%, respectively, while those for identifying the etiology of LGIB were 87.4%, 40.0%, 83.5, and 47.6%, respectively. CT was not inferior to lower endoscopy for active bleeding site detection. Early localization and the exclusion of active bleeding were possible with CT. Etiology was diagnosed with high sensitivity and PPV by CT. Thus, CT can be an alternative initial diagnostic tool for evaluating acute LGIB.